ANALISIS KETERLAMBATAN BICARA ANAK DALAM PERKEMBANGAN BAHASA PADA USIA 5-6 TAHUN - Putri Clawson; Winda Saputri (P3M STKIP 'Aisyiyah Riau, 2018)
This research is a qualitative descriptive study. The place of research is in kindergarten TK Negeri Pembina 1 Pekanbaru. The subjects of this study were 1 child who experienced delays in speech and TK Negeri Pembina 1 Pekanbaru Kindergarten teachers. The object of this study is the Delay in Children's Talk in Language Development at the Age of 5-6 Years in TK Negeri Pembina 1 Pekanbaru. Data collection techniques with observation and interview techniques. Based on the results of the study it can be concluded that the Kindergarten 1 Pekanbaru teacher kindergarten class, when learning children experience less listening or not listening when the teacher explains. When asked, it is necessary to repeat several times the new question he answered. When giving an answer the child only answers with a few words. When the child is called by his mother sometimes does not respond, it is necessary to call several times before he responds. When spoken to children sometimes only answer a few words of questions from his mother sometimes he also does not answer just stay quiet. When asked the questions he often does, he answers with answers yes or already. Like doing homework, eating, and taking a shower.